Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979361
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing genomic learning through tabletop interaction

Abstract: We present G-nome Surfer 2.0, a tabletop interface for fostering inquiry-based learning of genomics. We conducted an experimental study with 48 participants that compared students' learning of genomic concepts using existing bioinformatics tools and using two alternative implementations of G-nome Surfer: a collaborative multimouse GUI and a tabletop interface. Our findings indicate that G-nome Surfer improves students' performance, reduces workload, and increases enjoyment. The comparison of tabletop and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 28 publications
2
106
0
5
Order By: Relevance
“…Involv [24] and DeepTree [11] are tabletop interfaces for exploring the Encyclopedia of Life that are aimed at informal science learning settings. G-nome Surfer is a tabletop interface for collaborative exploration of genomic information [44,45,46]. In this work, we go beyond information exploration and delve into the design and specification of new biological systems.…”
Section: Reality-based Interfaces For Scientific Discovery and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Involv [24] and DeepTree [11] are tabletop interfaces for exploring the Encyclopedia of Life that are aimed at informal science learning settings. G-nome Surfer is a tabletop interface for collaborative exploration of genomic information [44,45,46]. In this work, we go beyond information exploration and delve into the design and specification of new biological systems.…”
Section: Reality-based Interfaces For Scientific Discovery and Educationmentioning
confidence: 99%
“…Several studies indicate that large interactive surfaces support collaboration through visibility of actions and egalitarian input [25,30], facilitate active reading [33], and foster the use of motor-spatial strategies, potentially lowering mental workload [36,4]. It has also been shown that multi-touch tabletops promote reflection and collaboration in learning environments [21,37,45,52]. Considering these findings as well as the increasing availability and falling prices of commercial hardware platforms, we decided to utilize multi-touch interaction with a large vertical interactive surface to address the requirements discussed above.…”
Section: The Moclo Planner Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although there are a number of research studies on collaborative learning discussions and verbal participations, (e.g. Flecker et al, 2009;Shaer et al, 2011), there is almost no research that had correlated the number and state of team member's suggestions (i.e., accepted or not accepted) with team diversity attributes, collaboration styles, and team performance.…”
Section: Introductionmentioning
confidence: 99%
“…Using the operational definitions and models of (1) collaboration profiles (Shaer et al, 2011), (2) collaboration process scaling (Meier, Spada, & Rummel, 2007), (3) collaborative learning mechanisms framework (Flecker et al, 2009), and (4) multi-level diversity and team mental model similarity (Fisher et al, 2012;Harrison, Price, & Bell, 1998;Miliken & Martins, 1996), this paper reports sets of results concerning the association between various diversity dimensions and collaboration style and team performance. In particular, dimensions of diversity include those that pertain to demographic (gender, race, and native language), academic (status and discipline), and use experience.…”
Section: Introductionmentioning
confidence: 99%